Stéréotypes nationaux et création romanesque dans «Á la Recherche du temps perdu» - Fraisse, Luc (Wydawnictwo Naukowe UAM, 2003)
In his novel cycle Á la recherche du temps perdu (1913-1927), Marcel Proust takes up a long-lasting process of psychological analysis carried on in the first person. This person represents, in a way, human nature and the reader's thought as well. Therefore, it seems that the question of national stereotypes should not have found its place in this kind of work, in which the fundamental psychological project did not allow the author to caricature national particularisms. Yet, they do find their incarnations in the whole series of characters (Poznań archives enable us to show even the hidden source of one of them) in order to subject this stereotypical vision to analysis and more profound criticism. What is peculiar, however, is that in the final analysis, prejudices against foreign nations are positively re-assessed because they help to understand the nature of the novelist's vision and literary activity.
National stereotypes and literary creation in Á la recherche du temps perdu
Keywords: Proust Marcel; Á la recherche du temps perdu